Analysis of solar photo‐voltaic for grid integration viability in Uganda - Chrish, Kavuma; Diego, Sandoval; Hakizimana, Khan Jean deDieu (John Wiley & Sons, Inc, 2022)
This study aimed to analyzing grid‐connected solar PV in Uganda for viability by evaluating the performance ratio of the already‐installed solar systems, and how flexible is the grid to accommodate more power from solar. The data collected from the solar plants included array size, type and rating of each module, array output, cell efficiency, DC to AC ratio, systems capital cost per watt, annual maintenance cost, inverter size and efficiency, array tilt, records of monthly solar irradiation, monthly energy produced, capital costs, operational costs and cost of a unit supplied to the grid. The System Advisor Model was used to analyze the technical and economic performances of solar plants in Uganda. The projected solar penetration by the year 2021 was 6.1%. The total annual energy was estimated at 69.52 GWh. The capacity factor ranges from 13.1% to 17.5% and a performance ratio of 0.76, and are within the recommended values. The grid was flexible up to 25.8% to accommodate more solar energy without destabilizing the network. It is viable to invest in solar energy since all four plants showed a positive net present value. With the increasing electric power demand, existing electrical grids should have capacity to accommodate power from renewable energy generators. Increasing the injected solar energy on to the existing grid results into compromising the power quality and overall system reliability decline. This study focuses on the viability of solar PV supply option for a grid connection.
Keywords: grid integration, performance ratio, capacity factor, solar PV system, advisory model